Electron beam crosslinking of alginate/nanoclay ink to improve functional properties of 3D printed hydrogel for removing heavy metal ions. (15th July 2020) - Shahbazi, Mahdiyar; Jäger, Henry; Ahmadi, Seyed Javad; Lacroix, Monique
Graphical abstract: Highlights: Nanocomposite ink-based suspension formed a crosslinked network by irradiation copolymerization. Photo-crosslinked network could preserve hydrogel shape during 3D printing and maintain printed architecture. Crosslinked network formed by irradiation could improve hydrogel thermal stability upon 3D printing. Crosslinked printed hydrogels showed a notable adsorption capacity for metal ions. Abstract: A printable nanocomposite hydrogel was fabricated with intercalation of alginate into clay galleries followed by irradiation crosslinking graft copolymerization acrylic acid to remove inorganic micropollutants from wastewater. In this regard, nanocomposite-based ink was treated by electron beam irradiation (5–60 kGy), and then irradiated inks were printed using an extrusion-based printer. Structural investigates showed that ink suspension formed a crosslinked network upon irradiation, which could preserve its shape during printing and maintain 3D printed architecture. No additional post-print crosslinking was required due to the formation of free radical and remaining in printed hydrogels as shown by electron spin resonance. Printed hydrogels treated with 5 and 60 kGy irradiation experienced instrumental changes, while functional properties of 15–45 kGy irradiated samples were unaffected upon printing. Losing crystallinity and thermal instability of hydrogels after printing were inhibited through irradiation crosslinking. Metal ion adsorption capacity showed that crosslinked printed hydrogels effectively removed heavy metal ions with high-capacity and fast-responsive. Moreover, metal ions adsorption by printed hydrogels was not selective, thus they can be used to remove various metal ion pollutants from wastewater.